A radiochemical study of irreversible protein loss on high-performance liquid chromatography column frits - Sadek, Paul C.; Carr, Peter W.; Bowers, Larry D.; Haddad, Louis C. (Analytical biochemistry, 1985)
Much success has been achieved in the separation and purification of a wide range of proteins using various high-pressure liquid chromatography techniques. Quantitative analyses of proteins which require 100% mass recovery of the protein are still beset with problems, especially when the total injected amount of protein decreases to below 10 μg. Stainless-steel frits have been cited for their deleterious effects on chromatography in general. In addition, the frits have specifically been found to be a significant contributor to irreversible protein loss—particularly when protein sample sizes are on the order of 1 μg or less. The findings presented below should therefore be of concern to those using HPLC for protein work.